A novel experimental method for investigating secondary wetting. (2nd January 2021) - Dezellus, Olivier; Jacques, Bruno; Lacaze, Jacques; Noûs, Camille
ABSTRACT: This paper proposes a novel and simple technique to study secondary wetting for bimetallic systems characterised by almost perfect primary wetting. The main principle is to promote complete dissociation between primary and secondary wettings, avoiding the use of the conventional sessile drop technique and its variants. For the first time, evidence is thus obtained that secondary wetting occurs in aluminium alloys.